БОРГОВА ПОЛІТИКА У СИСТЕМІ ФІНАНСОВОГО ВИРІВНЮВАННЯ: ДОСВІД СУБНАЦІОНАЛЬНОГО РІВНЯ КРАЇН-ЧЛЕНІВ ОЕСР ДЛЯ УКРАЇНИ - Пйонтко, Наталія Богданівна (Науковий журнал «Світ фінансів», 2017)
Пйонтко Н. Б. Боргова політика у системі фінансового вирівнювання: досвід субнаціонального рівня країн-членів ОЕСР для України. Визначено чинники формування механізму боргового фінансування у системі фінансового вирівнювання субнаціонального рівня країн-членів ОЕСР. Здійснено порівняння досвіду боргового фінансування субнаціонального рівня відповідно до форми державного устрою країн-членів ОЕСР. Охарактеризовано особливості застосування боргових інструментів фінансового вирівнювання. Узагальнено обмеження щодо здійснення запозичень субнаціональним рівнем країн-членів ОЕСР. Надано рекомендації для вдосконалення боргової політики у системі фінансового вирівнювання субнаціонального рівня України. Пйонтко Н. Б. Долговая политика в системе финансового выравнивания: опыт субнационального уровня стран-членов ОЭСР для Украины. Определены факторы формирования механизма долгового финансирования в системе финансового выравнивания субнационального уровня стран-членов ОЭСР. Проведено сравнение опыта долгового финансирования субнационального уровня в соответствии с формой государственного устройства стран-членов ОЭСР. Охарактеризованы особенности применения долговых инструментов финансового выравнивания. Обобщены ограничения по осуществлению заимствований субнациональным уровнем стран-членов ОЭСР. Даны рекомендации по совершенствованию долговой политики в системе финансового выравнивания субнационального уровня Украины. Piontko N. Debt policy in a financial equalization system: experience of subnational level of the OECD member states for Ukraine. Introduction. Application of debt finance facility as a financial equalization tool is the significant source of financial resources’ raising for efficient current activities, as well as for social and economic development of subnational level of the OECD member states. As for Ukraine, where transfers still are the basic tool of financial equalization, a study of debt policy realization of subnational level of the OECD member states is relevant and required task for establishment of contemporary equalization system for subnational level of Ukraine.Purpose. Purpose of the paper is to determine special aspects of application of debt finance facility in the financial equalization system of subnational level of the OECD member states.Results. Basic factors of formation of the debt finance facility of subnational level of the OECD member states, such as accelerated urbanisation processes, widespread decentralisation, inefficiency and lack of conventional transfer finance were defined in the paper. Based on the performed comparison of experience of the debt finance of subnational level accordingly to government system of the OECD member states it was identified that the higher level of debt finance is noticed in federal states. Special aspects of application of prioritized debt tools of financial equalization, such as loans and debt securities, were described. It was defined that debt securities are the basic debt finance tool for advanced economies. Limitations of debt finance realization by subnational level of the OECD member states were generalized: adhering to a “golden rule” as for borrowings; a need in approval of borrowings by superior authorities; compliance with requirements on threshold amount of subnational debt, its ratio to GDP or subnational budget revenues etc. Conclusion. It was determined that consideration of the following fundamentals of successful completion of debt finance facility of the OECD member states, especially: targeting of raised funds exclusively to investment goals (compliance with a “golden rule” as for financing); priority in financing income-producing projects; realization of a facility for provision of state guarantees relating to municipal borrowings; development of project financing, as well as formation of specific finance institutions is significant component of the improvement system for debt policy of subnational level of Ukraine.